On Algebraic Basis of the Algebra of Symmetric Polynomials on lp(Cn). (30th October 2017) - Kravtsiv, Victoriia; Vasylyshyn, Taras; Zagorodnyuk, Andriy
Abstract : We consider polynomials on spaces l p C n, 1 ≤ p < + ∞, of p -summing sequences of n -dimensional complex vectors, which are symmetric with respect to permutations of elements of the sequences, and describe algebraic bases of algebras of continuous symmetric polynomials on l p C n .